First Clinical Experience of Venous Reconstruction With Autologous Vascular Prosthesis From the Sickle Ligament of the Liver With Partial Portosystemic Bypass Surgery - A. Yu. Anisimov; A. A. Anisimov; A. I. Andreev; R. A. Ibragimov; A. T. Garaev (Неотложная медицинская помощь, 2021)
Aim of study. Presentation of our own first clinical experience of venous reconstruction in portosystemic bypass surgery with the use of autologous vascular prostheses of the falciform ligament of the liver in the splenorenal position in a patient with portal hypertension syndrome in the outcome of liver cirrhosis of viral etiology.Material and methods. Clinical observation of a patient born in 1978 with a diagnosis of cirrhosis of the liver of viral etiology (HCV) Child-Pugh A (6). MELD 10 points. Inactive phase. Intrahepatic portal hypertension syndrome. Esophageal varices grade III according to A. G. Scherzinger, gastric varices type I (GOV1) according to Sarin. Condition after repeated recurrent esophageal-gastric bleeding. Due to the high risk of another bleeding, as a secondary prevention of esophageal-gastric bleeding, partial splenorenal anastomosis of “H” - type was performed with the use of an autologous vascular prosthesis of the falciform ligament of the liver in the splenorenal position.Results. A flap measuring 60.0x20.0 mm was cut from the falciform ligament of the patient’s liver. From the latter, after adjusting the size of the graft to the individual needs of the patient, an autologous conduit was formed. It was used as an insert in the formation of an “H” - type splenorenal anastomosis with the imposition of two end-to-side anastomoses between the splenic vein and one end of the conduit and between the left renal vein and the other end of the conduit. The patency of the anastomosis was checked using intraoperative sonography. In a satisfactory condition, the patient was discharged for outpatient follow-up treatment at the place of residence. At the moment of writing the article, the follow-up period was 8 months. The bleeding did not recur. No varicose veins were found in the esophagus and stomach during control endoscopic examinations. The patency of the splenorenal shunt was confirmed by ultrasound dopplerography.Conclusion. The first clinical experience of venous reconstruction with portosystemic bypass surgery using as a possible replacement of autologous vascular prostheses of the falciform ligament of the liver in the splenorenal position in a patient with portal hypertension syndrome in the outcome of cirrhosis of the liver of viral etiology gives hope for the possibility of further successful testing of this method of splenorenal bypass surgery to reduce the risk of bleeding from varicose veins.